Sentinel lymph node biopsy may be unnecessary for ductal carcinoma in situ of the breast that is small and diagnosed by preoperative biopsy. (28th August 2020) - Uemoto, Yasuaki; Kondo, Naoto; Wanifuchi-Endo, Yumi; Asano, Tomoko; Hisada, Tomoka; Nishikawa, Sayaka; Katagiri, Yusuke; Terada, Mitsuo; Kato, Akiko; Okuda, Katsuhiro; Sugiura, Hiroshi; Kato, Hiroyuki; et al.
Abstract: Background: Current guidelines do not recommend that sentinel lymph node biopsy is routinely performed for ductal carcinoma in situ ; thus, indications for sentinel lymph node biopsy in patients with ductal carcinoma in situ remain controversial. In this study, we investigated whether sentinel lymph node biopsy can be safely omitted when ductal carcinoma in situ has been diagnosed by preoperative biopsy. Methods: We retrospectively analysed sentinel lymph node metastasis rates and upstaging to invasive cancer in surgical specimens, performed receiver operating characteristic analysis for ductal carcinoma in situ lesion size and assessed correlations with preoperative clinicopathological factors of 277 patients with ductal carcinoma in situ diagnosed by preoperative biopsy at our institution. Results: Among 277 patients with sentinel lymph node biopsy, six (2.2%) had sentinel lymph node metastasis. All six were upstaged to invasive cancer by pathological examination of surgical specimens. In total, 69 patients (24.9%) were upstaged to invasive cancer. The mean size of ductal carcinoma in situ lesions on preoperative imaging was significantly larger for the 69 upstaged patients (50.0 mm) than for the non-upstaged patients (34.4 mm; P  < 0.0001). Of the 277 patients with sentinel lymph node biopsy, 117 (42.2%) had preoperative ductal carcinoma in situ lesions <31.8 mm, which was identified as the optimal cut-off size by receiver operating characteristic analysis. Of these 117 patients, 96 (82.1%, 95% confidence interval: 73.9–88.5%) could be safely omitted from sentinel lymph node biopsy because all of them remained as ductal carcinoma in situ and had negative sentinel lymph nodes at surgery. Conclusions: Size of ductal carcinoma in situ lesions on preoperative diagnostic imaging is a predictor of diagnosis of invasive cancer on pathological examination of surgical specimens. Sentinel lymph node biopsy may be unnecessary in ductal carcinoma in situ diagnosed by preoperative biopsy in patients with small lesions. Abstract : We concluded that sentinel lymph node biopsy may be unnecessary in ductal carcinoma in situ of the breast diagnosed by preoperative biopsy in patients with small lesions.